The Arts Learning Model of BPK2 (Creative Work Practice Learning) Activities (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
The study program of Drama, Dance and Music Arts (Sendratasik) of FBS Unesa often gets visits from various schools in the city of Surabaya and surrounding areas for specific purposes, one of which is SMA Negeri 6. SMAN 6 Surabaya is one of the schools that organizes Creative Work Practice Learning (BPK2) at Sendratasik FBS Unesa. So that the implementation of BPK2 activities runs optimally, an appropriate learning model is needed. The purpose of this study is to describe the art learning model in BPK2 activities at SMA Negeri 6 Surabaya in Sendratasik FBS Unesa. The Qualitative approach was used in this study, the subjects are 306 students of SMA Negeri 6 Surabaya, 20 lecturers, and 20 students of FBS Unesa. The object of research, art learning models in Creative Work Practices Learning Activities (BPK2). Location in Sendratasik FBS Unesa. Data collection techniques: observation, interviews, documentation Data analysis is done during data collection, interactive with flexible techniques. Research results: Learning art with BPK2 activities use a humanistic approach that is optimizing the potential and interest of students in art. Art learning material includes appreciation and creation. Project-based models and apretensive models are used to produce works until they are performed. Staging learning outcomes as projects that must be completed by students are carried out well until BPK2 activities become meaningful learning because the benefits continue to be felt when returning to school. This research is important to encourage freedom of learning, so that art education according to its function gives rise to student creativity.